(untitled) (INTERNATIONAL JOURNAL OF MANAGEMENT & INFORMATION TECHNOLOGY, 2012)
With more than 500 million subscribers, India is the second largest mobile phone market in the world after China. In the last decade, an average of 15 Telecom operators has started operations in India. The market has been flamboyant for Indian as well as Foreign investors. Many of them are entering through the Merger and Acquisition route. The Governing Regulatory Authorities have a responsibility that no irregularity occurs and that every investor is given equal opportunity. Spectrum which is a constrained essential input for mobile services is also highly fragmented leading to possible industry inefficiencies. This paper critically examines the Merger and Acquisition scenario in the Telecom industry in India and the current policy framework that provides policy prescriptions for the future.